Effect of sidaguri and jatropha on tooth microhardness and tooth surface: An in vitro evaluation using CLSM - Maria Tanumiharja; Nurhayaty Natsir; Indrya K. Mattulada; Hafsah Katu; Harun Achmad; Lukman Muslimin; Haerul Arsyad; Lukmanul H. Arma (Journal of Dentomaxillofacial Science, 2021)
Objective: The purpose of this study was to evaluate the effect of herbal alternatives, extract of sidaguri (sida rhombifolia) combine with extract of jatropha sap (jatropha curcas) application on microhardness and morphology of tooth surface. Material and Methods: Twelve upper first premolar teeth were used in this study, prepared to Class I box cavities, and were then allocated into 4 groups (n=3). Group 1-3 were treated groups, applied with combined extracts of a small dose (5 mg), medium dose (25 mg), and high dose (50 mg), while group 4 was the control group. The cavities were restored with composite resin, immersed in artificial saliva, and stored at room temperature for 14 days. The fillings and extracts were removed and cleaned under running tap water. The teeth were cut in a vertical direction towards the apex, sectioned into 1 mm thickness, and evaluated using Laser Scanning Microscope (LSM), then were examined for microhardness test. Results: All treated groups showed significantly lower microhardness than the control group. Tooth porosity was observed, and its extensiveness was affected by doses of extracts. Conclusion: The application of herbal alternatives (extract of sidaguri and jatropha) lowered the microhardness of tooth structure and caused tooth porosities.